2015
DOI: 10.1002/2015jd023819
|View full text |Cite
|
Sign up to set email alerts
|

Multiyear applications of WRF/Chem over continental U.S.: Model evaluation, variation trend, and impacts of boundary conditions

Abstract: Multiyear applications of an online‐coupled meteorology‐chemistry model allow an assessment of the variation trends in simulated meteorology, air quality, and their interactions to changes in emissions and meteorology, as well as the impacts of initial and boundary conditions (ICONs/BCONs) on simulated aerosol‐cloud‐radiation interactions over a period of time. In this work, the Weather Research and Forecasting model with Chemistry version 3.4.1 (WRF/Chem v. 3.4.1) with the 2005 Carbon Bond mechanism coupled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 97 publications
1
10
2
Order By: Relevance
“…No published benchmarks are available to judge the model's performance for precipitation. Based on previous applications of MM5 and WRF over various regions [36,37,40,66,67,[84][85][86][87][88][89], NMBs within 30% represent the precipitation performance by current models, which will be used as a benchmark for precipitation in this work. For chemical concentrations, Zhang et al [90] suggested good performance benchmarks of NMBs and NMEs within ±15% and 30% for O 3 and PM 2.5 .…”
Section: Evaluation Datasets and Protocolsmentioning
confidence: 99%
“…No published benchmarks are available to judge the model's performance for precipitation. Based on previous applications of MM5 and WRF over various regions [36,37,40,66,67,[84][85][86][87][88][89], NMBs within 30% represent the precipitation performance by current models, which will be used as a benchmark for precipitation in this work. For chemical concentrations, Zhang et al [90] suggested good performance benchmarks of NMBs and NMEs within ±15% and 30% for O 3 and PM 2.5 .…”
Section: Evaluation Datasets and Protocolsmentioning
confidence: 99%
“…The CB05‐MADE/VBS mechanism with aqueous‐phase chemistry is fully coupled to existing model treatments for different aerosol‐radiation‐cloud feedback processes such as the aerosol direct effect on shortwave radiation, aerosol indirect effects on cloud droplet number concentration (CDNC), and cloud effects on shortwave radiation (Wang et al, ; Yahya, He, & Zhang, ). To account for the aerosol direct effect, aerosol radiative properties such as aerosol optical depth (AOD), single scattering albedo, and asymmetry factors are initially calculated based on the approach devised by Fast et al () according to the Mie theory (Mie, ).…”
Section: Description Of Models Emissions and Observationsmentioning
confidence: 99%
“…In this case, insufficient titration reactions are related to underprediction of NO x emissions from biomass burning regions. The level of NO x can influence O 3 mixing ratios through titration chemistry during the night and in the early morning hours (Yahya, He, & Zhang, ). Comparisons between the observed and predicted concentrations of NO 2 at four CETESB sites are shown in supporting information Figure S4.…”
Section: Impacts Of Biomass Burning Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To derive a temporal allocation for monthly-averaged RCP emissions, hourly emissions profiles are taken from in-house WRF/Chem simulations over CONUS during 2001 (Yahya et al, 2015a), and 2006 and 2010 (Yahya et al, 2014(Yahya et al, , 2015b. For those existing in-house simulations, the emissions were generated with the Sparse Matrix Operator Kernel Emissions (SMOKE) model version 2.3 for 2002 NEI and SMOKE version 3.4 for 2008 NEI with year-specific sector emissions for 2006 and 2010, which prepare the spatially, temporally, and chemically speciated "model-ready" emissions.…”
Section: Processing Of Emissions and Initial Conditions (Ics)/boundarmentioning
confidence: 99%